Halal food industry in Thailand: History, prospects and challenges - Nawawi, M.S.A.M.; Wan Mohamed Radzi, C.W.J.; Mamat, M.Z.; Hasbullah, M.; Mokhtar, M.I.; Jenatabadi, H.S.; Man, S.; Azmah, O.; Azizan, S.A.; Pauzi, N. (2017)
The productions of halal food from farm to table are very challenging in our new modern world. Furthermore manufacturing in world halal food industry are also extremely competitive. Thailand has been listed as one of top rank in the world tourist destination, top medical hub for foreign patients and relative and it also has been listed as top tenth world biggestfood exporting countries and exporting halal products to the world. The main objective of this paper is to study the trend of producing halal food products, prospects, and current challenging in Thailand. The data analysis is included interview with some experts in Thailand halal food industry. This paper would be velY helpfulfor policy makers and producers of halalfood industry in East of Asia countries. The main contribution of this study is to bring out that how Thailand as a non-Muslim country is successful for producing and exporting halalfood production to the Middle East countries.